2015
DOI: 10.1111/1365-2435.12391
|View full text |Cite
|
Sign up to set email alerts
|

Is successional research nearing its climax? New approaches for understanding dynamic communities

Abstract: Summary1. Succession has been a focus of extensive ecological study for well over a century. Despite this sustained interest, succession remains a central theme in ecological research and is positioned to continue that prominence in this era of expanding human impacts. Community ecology is currently experiencing a profound conceptual expansion, providing many new insights into succession. 2. Here we present an existing conceptual framework of successional drivers that includes variation in site conditions, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(208 citation statements)
references
References 108 publications
(145 reference statements)
6
190
1
6
Order By: Relevance
“…Ecological succession thus continues to remain a central theme in ecological research in this era of ever-expanding human impacts and rapid landscape changes (Pickett et al 2009;Meiners et al 2015). There have been complex interactions between people and natural landscapes across the globe since the origin of humans (Luken 1990).…”
Section: Succession and Disturbancementioning
confidence: 99%
“…Ecological succession thus continues to remain a central theme in ecological research in this era of ever-expanding human impacts and rapid landscape changes (Pickett et al 2009;Meiners et al 2015). There have been complex interactions between people and natural landscapes across the globe since the origin of humans (Luken 1990).…”
Section: Succession and Disturbancementioning
confidence: 99%
“…Despite the fact that the successional process is not always unidirectional and can follow different routes [67,69] and operate according to different causes [70], for this study we considered the secondary succession only as the process of recovery of vegetation [66], without taking into account the route or factors that caused it. Therefore, for this purpose, those areas with modified land cover (for example crops and urban areas), without vegetation (bare soil areas), or characterized by fast-grow pioneer species (grasslands, sparse or dense herbaceous vegetation, among others) were selected as disturbance areas or primary successional stages.…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
“…4 and 5 revealed also no striking differences between the three treatments. Meiners et al (2015) suggested that the phylogenetic structure of a community develops from a random or clustered pattern at the start of succession to an overdispersed structure with increasing competition during succession. Similarly, Dinnage (2009) showed that disturbance lead to clustered species communities in old field systems.…”
Section: Phylogenetic Structurementioning
confidence: 99%
“…At the beginning of a succession, the most important process structuring communities is the arrival of propagules from outside as well as the germination from the soil seed bank. Therefore, both random processes (arrival) as well as environmental filtering (conditions for germination) are expected to dominate community assembly during the early stages of succession (Cavender-Bares et al, 2009;Meiners et al, 2015). As succession proceeds, interspecific competition is expected to increase in importance (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation